Knee crepitus is not associated with the occurrence of total knee replacement in knee osteoarthritis – a longitudinal study with data from the Osteoarthritis Initiative - Pazzinatto, Marcella Ferraz [UNESP]; de Oliveira Silva, Danilo [UNESP]; Azevedo, Fábio Mícolis de [UNESP]; Pappas, Evangelos (Elsevier, 2019)
Objective(s): To investigate whether the presence of knee crepitus is associated with the occurrence of total knee replacement (TKR), quality of life and deficits in physical function at long-term. Methods: Setting – This observational study uses longitudinal data (up to 4-year follow-up) from the Osteoarthritis Initiative (OAI). Participants – 4566 participants. Main Outcome Measure(s) – Logistic regression models were used to test if baseline knee crepitus is associated with the occurrence of TKR. Linear mixed models with adjustment for confounding variables (age, gender, BMI and Kellgren–Lawrence grade) were used to test the association between baseline knee crepitus and longitudinal changes in the pain, self-reported physical function, quality of life and performance-based function. Results: The presence of knee crepitus at baseline does not predict the occurrence of TKR at 36 months (p = 0.58 and 0.67 for right and left knees, respectively). The crepitus group presented a slightly knee extension strength decline from baseline to 48 months (p = 0.03 for the right and 0.01 for the left knee; between group difference = 2% for both right [95%CI = −0.12; −0.01] and left knees [95%CI = −0.13; −0.02]). Conclusion: The presence of knee crepitus is not associated with the occurrence of TKR in the following three years. Knee crepitus is associated with slightly declines in knee extension strength, but this does not seem to affect physical function and quality of life at long-term.
Keywords: Knee; Knee osteoarthritis; Quality of life; Recovery of function